Mutual Coupling Reduction of a Wideband Circularly Polarized Microstrip MIMO Antenna - Adam, Ismahayati; Mohd Yasin, Mohd Najib; Ramli, Nurulazlina; Jusoh, Muzammil; Rahim, Hasliza A.; Latef, Tarik Abdul; Tengku Mohmed Noor Izam, Tengku Faiz; Sabapathy, Thennarasan (Institute of Electrical and Electronics Engineers, 2019)
Mutual coupling (MC) between elements in an antenna array could significantly affect antenna performance, but this effect has rarely been reported for circularly polarized (CP) antennas. Therefore, this paper investigates a wideband CP multiple-input-multiple-output (MIMO) antenna operating between 1.8 and 2.6 GHz. A line patch was introduced between closely placed radiating elements ( 0.3λ ) to produce a high isolation between elements in the proposed antenna. The designed MIMO antenna has a wide impedance bandwidth, a wide axial ratio (AR) bandwidth, a very low MC ( \text{S}-{{21}} < -25 dB), a low envelop correlation coefficient (ECC < 0.01), a high diversity gain (DG 10 dB), and a realized gain of above 2 dB over the entire frequencies. The prototype of the proposed antenna geometry was fabricated and measured. A good agreement between the simulated and measured results was observed. © 2013 IEEE.